2021
DOI: 10.1038/s41598-021-82247-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional coupling and repair of 8-OxoG activate a RecA-dependent checkpoint that controls the onset of sporulation in Bacillus subtilis

Abstract: During sporulation Bacillus subtilis Mfd couples transcription to nucleotide excision repair (NER) to eliminate DNA distorting lesions. Here, we report a significant decline in sporulation following Mfd disruption, which was manifested in the absence of external DNA-damage suggesting that spontaneous lesions activate the function of Mfd for an efficient sporogenesis. Accordingly, a dramatic decline in sporulation efficiency took place in a B. subtilis strain lacking Mfd and the repair/prevention guanine oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As shown in this work, these processes can be subjected to regulation with Mfd ( Figure 2 ), a transcription factor commonly associated with the repair of bulky DNA lesions in bacteria [ 81 ]. However, recent evidence has revealed that Mfd functions as a global regulator of gene transcription and cell differentiation in B. subtilis [ 34 , 82 ]. Therefore, elucidating the Mfd-dependent mechanisms that cells employ to directly or indirectly regulate the expression of the factors associated with the HPM and HPHR phenotypes will contribute to understanding the novel aspects of bacterial physiology in stressed bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in this work, these processes can be subjected to regulation with Mfd ( Figure 2 ), a transcription factor commonly associated with the repair of bulky DNA lesions in bacteria [ 81 ]. However, recent evidence has revealed that Mfd functions as a global regulator of gene transcription and cell differentiation in B. subtilis [ 34 , 82 ]. Therefore, elucidating the Mfd-dependent mechanisms that cells employ to directly or indirectly regulate the expression of the factors associated with the HPM and HPHR phenotypes will contribute to understanding the novel aspects of bacterial physiology in stressed bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The strain B. subtilis PS832 (Wild-type trp + revertant of strain 168 [ 35 ]), and its derivative, PERM603 ( ytkD :: neo mutM :: tet mutY :: sp . Neo R Tc R Sp R ∆GO; [ 34 ]), were employed in this study. The routinely used growth medium was the Luria–Bertani (LB) medium.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations